LUIS PANCORBO CRESPO, INÉS MARTÍN ROBLES - A. Lawrence Kocher. American Architect - Delgado Orusco, Eduardo (ZARCH, 2025)
LUIS PANCORBO CRESPO, INÉS MARTÍN ROBLES A. Lawrence Kocher. American Architect Applied Research + Design, San Francisco-USA, 2025, 380 pp. Tapa dura. 60.00 Idioma: inglés ISBN: 978-1-961856-61-5